HUBUNGAN ANTARA KELOMPOK TEMAN SEBAYA DENGAN GAYA HIDUP HEDONIS - Itryah, Itryah (Jurnal Ilmiah Psyche, 2015)
This study aimed to investigate relationship between peer group with hedonis on student Law evening Major 2009 and 2010 of University Sriwijaya Palembang. Dependent variable in this study is a Hedonis life style, while peer group an independent variable. This research uses a scale of Hedonis life style and peer group.  This research uses quantitative methods. The sample used 113 students Law evening Major 2009 and 2010 of University Sriwijaya Palembang, with random sampling methode. The results of this research showed a significant relationship between peer group with Hedonis life on student Law evening Major 2009 and 2010 of University Sriwijaya Palembang with a value of r = 0.726, F = 123.670, p = 0.000 for the results of significance (p) 0.000 mean value of p <0.01. So otherwise there is a very significant relationship. Peer group contributes to Hedonis life style  of 52.7%. Thus there are another 47.3% contributed by another factors that could trigger Hedonis life style on student Law evening Major 2009 and 2010 of University Sriwijaya Palembang.